NGAJI SOSMED TANGKAL PEMAHAMAN RADIKAL MELALUI PENDAMPINGAN KOMUNITAS LANSIA DENGAN SAJIAN PROGRAM NGABARI DI DESA SUKOREJO SUKOWONO JEMBER - Hosaini Hosaini (LP2M Universitas Ibrahimy, 2020)
This outreach program is carried out in Sukurejo village in Sukowono, Jember with an agrarian society. The method used is the location survey. They are finding out the problems experienced by the community to local community leaders and submitting proposals, involving students or members of the team, coaching and planning the implementation of